Uso abusivo dos tratados internacionais no planejamento Tributário - Nejm, Paulo Bassil Hanna (2019)
This dissertation aims to analyze the abusive use of international treaties for tax planning purposes. And to fulfill this purpose we approach the main concepts and institutes related to the theme, analyzing the legal norms of domestic law that allow and limit the exercise of tax planning activity. We also analyze how tax planning occurs with the use of international treaties. And finally, we investigate what makes this practice abusive, and ways to curb abuse by using treaties to execute tax planning